2022
DOI: 10.3389/fpsyg.2022.760102
|View full text |Cite
|
Sign up to set email alerts
|

CEO Overconfidence and Corporate Innovation Outcomes: Evidence From China

Abstract: This study examines how chief executive officer (CEO) overconfidence can influence the quantity, quality and direction of corporate innovation using Chinese firms for the period 2009–2016. Our results suggest that overall, CEO overconfidence has a positive impact on firm innovation productivity. Furthermore, this effect is significant for Chinese non-SOEs but not for Chinese SOEs. Specifically, an overconfident CEO can facilitate firm innovation in new technological areas but not in the firm’s existing areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Previous studies have mainly focused on the effect of executives’ demographic characteristics on innovation activities ( Hambrick, 2007 ; Lin et al, 2011 ; Heyden et al, 2017 ). Recently, scholars have investigated how strategy decisions and activities are directly influenced by psychological traits, including overconfidence, narcissism, and hubris ( Park et al, 2018 ; Tang et al, 2018 ; Li and Zhang, 2022 ; Wang et al, 2022 ). In line with these studies in the subfield of innovation management, we explored the impact of CEOs’ celebrity status on firm innovation investment by suggesting social status as a behavioral reference for decision-making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have mainly focused on the effect of executives’ demographic characteristics on innovation activities ( Hambrick, 2007 ; Lin et al, 2011 ; Heyden et al, 2017 ). Recently, scholars have investigated how strategy decisions and activities are directly influenced by psychological traits, including overconfidence, narcissism, and hubris ( Park et al, 2018 ; Tang et al, 2018 ; Li and Zhang, 2022 ; Wang et al, 2022 ). In line with these studies in the subfield of innovation management, we explored the impact of CEOs’ celebrity status on firm innovation investment by suggesting social status as a behavioral reference for decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, celebrity CEOs have great confidence in their abilities relevant to innovation strategy ( Lovelace et al, 2018 ), and they may be more likely to overestimate the probability of success and profitability from investing in new products ( Camerer and Lovallo, 1999 ). Previous research has suggested that there is a positive and significant correlation between overconfident CEOs and innovation input ( Li and Zhang, 2022 ). Hence, we argue that celebrity CEOs are more likely to increase innovation investment, compared to non-celebrity CEOs.…”
Section: Theoretical Model and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, should these high-level directors in the informal hierarchy choose intense R&D activities to pursue innovation quality, any failure would not only result in significant company losses but, more importantly, expose them to senior administrative accountability. This could adversely affect their later promotion prospects and the maintenance of their informal status within the board (Li and Zhang, 2022). For non-SOEs, they face intense domestic market competition and must rely on enhancing innovation quality to surpass pure price competition, capturing long-term growth points in performance (Chen et al, 2020).…”
Section: Moderating Effect Of Property Rights Naturementioning
confidence: 99%